Reducing Uncertainties in Carbonate Clumped Isotope Analysis Through Consistent Carbonate‐Based Standardization - Stefano M. Bernasconi; Inigo A. Müller; Kristin D. Bergmann; Sebastian F. M. Breitenbach; Alvaro Fernandez; David A. Hodell; Madalina Jaggi; Anna Nele Meckler; Isabel Millan; Martin Ziegler (Geochemistry, Geophysics, Geosystems, 2018)
Abstract About a decade after its introduction, the field of carbonate clumped isotope thermometry is rapidly expanding because of the large number of possible applications and its potential to solve long‐standing questions in Earth Sciences. Major factors limiting the application of this method are the very high analytical precision required for meaningful interpretations, the relatively complex sample preparation procedures, and the mass spectrometric corrections needed. In this paper we first briefly review the evolution of the analytical and standardization procedures and discuss the major remaining sources of uncertainty. We propose that the use of carbonate standards to project the results to the carbon dioxide equilibrium scale can improve interlaboratory data comparability and help to solve long‐standing discrepancies between laboratories and temperature calibrations. The use of carbonates reduces uncertainties related to gas preparation and cleaning procedures and ensures equal treatment of samples and standards. We present a set of carbonate standards of diverse composition, discuss how they can be used to correct for mass spectrometric biases, and demonstrate that their use significantly improves the comparability among four laboratories. We propose that the use of these standards or of a similar set of carbonate standards will improve the comparability of data across laboratories.